The Character Adaptation of Masked Puppet Figures in Ruwatan Ritual - Hidajat, Robby (Harmonia: Journal of Arts Research and Education, 2016)
One myth that is believed by people living in Duwet village is distress that threatens human beings from when they are born till the day they die. As one way to overcome the distress, people, especially those who are living in Duwet village, hold ritual called as tolak bala. One step in the ritual is self-cleaning oneself from distress or sukerta. In addition to the ritual is a masked puppet as a means of the ritual execution. Thus, this study aims at finding out the functions of the Ruwatan masked puppet. Functional-structural perspective was adopted in the study by implementing observation, interview, and documentation study techniques. Results show that masked puppet has a special function which is to serve as a means of Ruwatan that is specifically to obtain society participation in order to give spiritual support to the process of ritual as a whole tolak bala or distress expulsion process.